Core domain set for hidradenitis suppurativa trial outcomes. (17th September 2018) - Thorlacius, L.; Ingram, J.R.; Villumsen, B.; Esmann, S.; Kirby, J.S.; Gottlieb, A.B.; Merola, J.F.; Dellavalle, R.; Nielsen, S.M.; Christensen, R.; Garg, A.; Jemec, G.B.E.; et al.
Summary: Hidradenitis suppurativa (HS) is a skin condition that causes painful swollen red bumps in the folds of the body (underarms, under breasts, groin, and buttocks). It can be mistaken for bacterial abscess or boils, but HS is not caused by bacteria. HS occurs in about 0.1% to 4% of people worldwide. This study aimed to find out what clinical trials for HS should measure, such as symptoms (e.g. pain, itch), physical changes (e.g. skin redness or swelling), or impact on people's lives (e.g. quality of life). To do this, the study included two groups: people with HS and healthcare providers (physicians, pharmaceutical industry representatives, and regulatory representatives) and conducted online surveys and in‐person meetings with presentations and discussions as well as surveys to gather opinions on which measures to include. Thirteen countries and four continents were represented. The result of the meetings, discussions, and surveys showed that at least 70% of the people with HS and healthcare providers recommended that clinical trials include measures of: (1) pain (2) physical changes due to HS (e.g. redness); (3) quality of life changes due to HS specifically; (4) changes in the course of HS (e.g. flare‐ups) (5) global rating (i.e. overall rating, considering everything, of the severity of the condition) and (6) other symptoms (fatigue and drainage). This work is important because it included many different types of people who contribute to HS treatment, including the people who have HS, develop or regulate treatments, and treat people with HS. More work is coming and it will focus on how to measure in trials treating HS (what instruments to use). Abstract : Linked Article:  Thorlacius et al. Br J Dermatol 2018;179 :642–650